Optic disc edema during strict 6° head-down tilt bed rest is related to one-carbon metabolism pathway genetics and optic cup volume - Zwart, Sara R.; Macias, Brandon R.; Laurie, Steven S.; Ferguson, Connor; Stern, Claudia; Suh, Alex; Melin, M. Mark; Young, Millennia; Bershad, Eric; Smith, Scott M. (Frontiers in Ophthalmology, 2023)
Some astronauts on International Space Station missions experience neuroophthalmological pathologies as part of spaceflight associated neuro-ocular syndrome (SANS). Strict head-down tilt bed rest (HDTBR) is a spaceflight analog that replicates SANS findings and those who had 3–4 risk alleles (G and C alleles from the methionine synthase reductase [MTRR] A66G and serine hydroxymethyltransferase [SHMT1] C1420T, respectively) as compared to 1-2 risk alleles, had a greater increase in total retinal thickness (TRT). The objective of this study was to identify factors that contribute to the individual variability of the development of SANS in a 60 d HDTBR at the German Aerospace Center’s:envihab facility, Cologne Germany. 22 of 24 subjects who participated in the HDTBR study provided blood samples for genetic analysis. Total retinal thickness and optic cup volume were measured before and after bed rest. Subjects with 3–4 versus 0-2 risk alleles had greater ΔTRT during and after bed rest, and the model improved with the addition of baseline optic cup volume. This bed rest study confirms that variants of MTRR and SHMT1 are associated with ocular pathologies. Subjects with more risk alleles had the greatest HDTBR-induced ΔTRT, reaffirming that genetics predispose some individuals to developing SANS. Preflight optic cup volume and genetics better predict ΔTRT than either one alone. Whether nutritional supplements can override the genetic influences on biochemistry, physiology, and pathophysiology remains to be tested. These findings have significant implications for both aerospace and terrestrial medicine.